A Study On The Method Of Teaching Speaking At The First Year Of SMPN 2 Jumapolo In 2012/2013 Academic Year - Rahayu, Dyah Sholihati; , Drs. Djoko Srijono, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
This research aims at describing the method of teaching speaking at the first year of SMPN 2 Jumapolo in 2012/2013 academic year. The objectives of the study are to describe: 1) the English teaching method applied by the teacher to improve students‟ speaking skill during the lesson, 2) the problems faced by the students during English speaking class, and 3) method/techniques used by the teacher to overcome the problems. The research is a descriptive research. The writer collets the data by observing teachinglearning process, conducting the interview, and documenting some important data that support to this research. The data are from interview script, field note, syllabus, text book, and lesson plan. The methods of collecting data are observation, interview, and documentation. The techniques of analyzing data are reduction the data, data analysis, display the data, and conclusion and verification. The result of the research are: 1) the method implemented by the teacher in teaching speaking are role play, circle chat games, and guessing game technique; 2) the approach adopted by the teacher in learning process is constructivism theory; 3) The roles of the teacher were as a planner, manager, facilitator, and motivator. While the students became the subject of the learning process; 4) The most problems faced by the students are the lack of vocabulary, the difficulty in pronunciation, and the students‟ nervousness and shyness; 5) To overcome the problems faced by the students, the teacher asked the students to write the new word on a whiteboard; created a learning situation that is challenging, stimulated the students by using games, discussion, and role play; created a pleasant relationship between teacher to students and students to students; and asked the students to repeat the teacher in pronouncing some words to justify the pronunciation.